Analisis Tantangan Dan Pembaharuan Dalam Perhitungan Harga Pokok Produksi Pada Umkm Chicken Steak Di Yogyakarta Dengan Metode Full Costing - Dinna Nur Azizah Sulistyowati (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
This study aims to evaluate the impact of direct material costd, direct labor costs, and factory overhead costd on the cost goods manufactured at a Chicken Steak MSME in Yogyakarta using the full costing method. The background to this study is that many MSMEs determine production prices using simplistic methods without considering all cost elements, resulting in inaccurate selling prices. The research findings indicate that, individually, direct material costs, direct labor costs, and factory overhead costs have a significant impact on the cost of goods manufactured. Furthermore, these three independent variables simultaneously have a significant influence on the cost of goods manufactured. This confirms that the application of the full costing method can provide more comprehensive and accurate insights into production costs,allowing SMEs to make more accurate pricing decisions and optimize profitability.